EVALUATION THE LEVEL OF SERVICE IN THE BAGGAGE CLAIM AREA ON PASSENGER SATISFACTION AT THE AIRPORT INTERNATIONAL MINANGKABAU USING THE IMPORTANCE PERFORMANCE ANALYSIS METHOD - Yogaswara, Syahril Asfah; Iswahyudi, Prasetyo; Fatimah, Siti (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Minangkabau International Airport is in West Sumatra, more precisely in Pariaman Regency. This airport has several terminals, namely Domestic Terminal, International Terminal, VIP Terminal and Cargo Terminal. At the domestic terminal at Minangkabau Airport, baggage claim facilities and several other facilities are quite good but are considered to be lacking during peak passenger hours. This research aims to determine the priority attributes for improvement from terminal operators to airport service users. This research uses a quantitative approach method where data is collected through observation, distributing questionnaires, and literature study. The guidelines used are Ministerial Regulation no. 178 of 2015 concerning service standards for airport service users. Questionnaires were distributed to 50 incoming passenger respondents who immediately experienced the facilities available in the baggage claim area of Minangkabau International Airport. Then the data from the research results was processed using the SPSS application. The data processing methods used are Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Based on the CSI Customer Satisfaction Index analysis, the passenger satisfaction index is 84.17%, this illustrates that passengers are very satisfied with the performance of the services provided. The results of the Cartesian Importance-Performance Analysis IPA diagram analysis show that there are four attributes which are the main priority to be improved, namely the size of the baggage claim area, the availability of trash cans, the availability of seats in the baggage claim area, and the cleanliness of the baggage claim area.